Inclusive Beauty Campaign: Redefining Beauty Standards in Indonesian Beauty Product Advertising - Intan Cahya Amanda; Tuty Handayani (Journal of Language and Literature, 2026)
This research analyzes how inclusive beauty is constructed in the advertisement of a local Indonesian brand, Rosé All Day, using John Fiske’s three levels of semiotic analysis: reality, representation, and ideology. This study not only analyzes how the ad promotes inclusive beauty but also sees the campaign as a challenge of conventional beauty standards which has been going on for centuries. This research applies a qualitative method. Data was collected from selected scenes, focusing on elements such as appearance, makeup, clothing, gestures, camera work, lighting, and slogans. Analysis revealed that the advertisement features models with diverse skin tones, facial features, and body types, reinforcing that beauty belongs to all women regardless their differences. At the level of reality, the ad features models with minimal makeup and visible facial textures, which emphasizes natural beauty. At the level of representation, soft lighting, pastel color palettes, and close-up shots are used to create a soothing and intimate tone. On an ideological level, the campaign promotes a message of self-love and authenticity, challenging the dominant ideals of beauty in Indonesian media that often prioritize light skin and slim body. The slogan “Bring Out #TheRealestYou” encourages viewers to embrace their true selves and redefine beauty as personal expression rather than conformity. This research contributes to the discussion on beauty representations in the media and demonstrates how advertising can serve as a platform to promote inclusive beauty.